Omega-3- and Resveratrol-Loaded Lipid Nanosystems for Potential Use as Topical Formulations in Autoimmune, Inflammatory, and Cancerous Skin Diseases - Ana R. Caldas; José Catita; Raul Machado; Artur Ribeiro; Fátima Cerqueira; Bruno Horta; Rui Medeiros; Marlene Lúcio; Carla M. Lopes (MDPI AG, 2021)
Resveratrol (RSV) and omega 3 (ω3), because of their biological favorable properties, have become subjects of interest for researchers in dermocosmetic and pharmaceutical industries; however, these bioactives present technological limitations that hinder their effective delivery to the target skin layer. To overcome the stability and skin permeation limitations of free bioactives, this work proposes a combined strategy involving two different lipid nanosystems (liposomes and lipid nanoparticles) that include ω3 in their lipid matrix. Additionaly, RSV is only encapsulated in liposomes that provid an adequate amphiphilic environment. Each formulation is thoroughly characterized regarding their physical-chemical properties. Subsequently, the therapeutic performance of the lipid nanosystems is evaluated based on their protective roles against lipid peroxidation, as well as inhibition of cicloxygenase (COX) and nitric oxid (NO) production in the RWA264.7 cell line. Finally, the lipid nanosystems are incorporated in hydrogel to allow their topical administration, then rheology, occlusion, and RSV release-diffusion assays are performed. Lipid nanoparticles provide occlusive effects at the skin surface. Liposomes provide sustained RSV release and their flexibility conferred by edge activator components enhances RSV diffusion, which is required to reach NO production cells and COX cell membrane enzymes. Overall, the inclusion of both lipid nanosystems in the same semisolid base constitutes a promising strategy for autoimmune, inflammatory, and cancerous skin diseases.